Does Small High School Reform Lift Urban Districts? Evidence From New York City. (April 2015) - Stiefel, Leanna; Schwartz, Amy Ellen; Wiswall, Matthew
Research finds that small high schools deliver better outcomes than large high schools for urban students. An important outstanding question is whether this better performance is gained at the expense of losses elsewhere: Does small school reform lift the whole district? We explore New York City's small high school reform in which hundreds of new small high schools were built in less than a decade. We use rich individual student data on four cohorts of New York City high school students and estimate effects of schools on student outcomes. Our results suggest that the introduction of small schools improved outcomes for students in all types of schools: large, small, continuously operating, and new. Small school reform lifted all boats.